Here,
{sqrt(3)+sqrt(2)}^x + {sqrt(3)-sqrt(2)}^x =10
=>(sqrt3+sqrt2)^x+(((sqrt3-sqrt2)
(sqrt3+sqrt2))/((sqrt3+sqrt2)))^x=10
=>(sqrt3+sqrt2)^x+((3-2)/((sqrt3+sqrt2)))^x=10
Taking, color(blue)((sqrt3+sqrt2)^x=m, we get
m+(1/m)=10
=>m^2+1=10m
=>m^2-10m=-1
=>m^2-10m+25=25-1=24
=>(m-5)^2=(2sqrt6)^2
=>m-5=+-2sqrt6
=>m=5+-2sqrt6
++=>m=(3+-2sqrt(3xx2)+2)
=>m=(sqrt3)^2+-2sqrt3sqrt2+(sqrt2)^2
=>m=(sqrt3+-sqrt2)^2
But ,we have taken color(blue)(m=(sqrt3+sqrt2)^x
So,
(sqrt3+sqrt2)^x=(sqrt3+sqrt2)^2
or(sqrt3+sqrt2)^x=(sqrt3-sqrt2)^2 =(1/(sqrt3+sqrt2))^2
i.e.(sqrt3+sqrt2)^x=(sqrt3+sqrt2)^2or(sqrt3+sqrt2)^x=
(sqrt3+sqrt2)^-2
Comparing we get,
x=2or x=-2